RELATIONSHIP BETWEEN CONSUMPTION AND FE TABLET HEMOGLOBIN CONTENT IN PREGNANT WOMEN TRIMESTER III KALIKEBO, TRUCUK, KLATEN - KLATEN, STIKES DUTAGAMA (STIKES DUTAGAMA KLATEN, 2012)
BACKGROUND = The frequency of occurrence of pregnancy anemia in Indonesia is still high at around 40.1% in 2010 (IDHS 2010). January 2010 to December 2010 there were some 29 263 pregnant women in Klaten people with mild anemia criteria of 2425 people, 308 people were anemia and severe anemia 20. (DKK Klaten, 2010). Based on preliminary surveys in rural areas kalikebo in May 2011, earned third trimester pregnant women as many as 35 people, found 19 people classified as mild anemia and six people classified as moderate anemia (MCH Trucuk Health Center, 2011). These frequencies it is still quite high, it needs more intensive countermeasures to prevent the occurrence of anemia in pregnancy.The research objectives = To determine the relationship between fe tablet consumption and hemoglobin levels in pregnant third trimester region Kalikebo Trucuk, Klaten, by age, education and employment of pregnant women.Research Methods = Using the method of correlation with the approach diskrptif Cross Sectional. The study population was all pregnant women who are 32 third trimester of the respondent. Data collection techniques using koesioner who have gone through the test of validity and reliability,and performed the data analysis were processed using SPSS.16, and presented in tabular form.Results = Stats of the research results chi square test (x ²) x ² values obtained count = 21 961 on df = 1 with a rate of 5% obtained belief table x ² = 3.841 with the probability value p = 0.000, which means p <0.05.Conclusion = There is a relationship between consumption and tablet fe trimester maternal levels of hemoglobin III region Kalikebo village, District trucuk, Klaten majority of respondents consuming fe tablet correctly and hemoglobin> 11gr% of 15 persons (46.875%), and do not have anemia in pregnancy . This is because the factors age, education and employment.